2011
DOI: 10.1186/1471-2458-11-240
|View full text |Cite
|
Sign up to set email alerts
|

Development of burnout over time and the causal order of the three dimensions of burnout among male and female GPs. A three-wave panel study

Abstract: BackgroundA good understanding of the aetiology and development of burnout facilitates its early recognition, prevention and treatment. Since the prevalence and onset of this health problem is thought to differ between men and women, sex must be taken into account. This study aims to assess the prevalence and development of burnout among General Practitioners (GPs). In this population the prevalence of burnout is high.MethodsWe performed a three-wave longitudinal study (2002, 2004, 2006) in a random sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
123
3
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(165 citation statements)
references
References 44 publications
23
123
3
16
Order By: Relevance
“…For example, in the present study, female students endorsed higher distress from their exposure to human suffering than male students. This is consistent with previous research demonstrating that female physicians are more likely to experience emotional exhaustion at the onset of burnout, compared to male physicians who experience depersonalization as the initial symptom [27]. Similarly, female students in the present study reported more difficulty managing their academic workload and more problems with time management.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the present study, female students endorsed higher distress from their exposure to human suffering than male students. This is consistent with previous research demonstrating that female physicians are more likely to experience emotional exhaustion at the onset of burnout, compared to male physicians who experience depersonalization as the initial symptom [27]. Similarly, female students in the present study reported more difficulty managing their academic workload and more problems with time management.…”
Section: Discussionsupporting
confidence: 92%
“…Among Swedish police personnel (Backteman-Erlanson et al, 2013), the mean value for DP was also significantly higher for men than for women. These results are also consistent with other studies that report men to have higher levels of DP than women (Houkes, Winants, Twellaar, & Verdonk, 2011). This result is also comparable to established research in the field (Bakker, Demerouti, & Schaufeli, 2002;Emmerik & Euwema, 2001;Maslach et al, 2001;Schaufeli & Enzmann, 1998).…”
Section: Discussionsupporting
confidence: 82%
“…With regard to the differences between women and men in this study, a problem with studying sex differences in a male-dominated profession is that the sample sizes for females are generally small resulting in poor power to detect small differences between the sexes (Greenglass, 1991;Greenglass, Burke, & Ondrack, 1990;Grossi, Perski, EvengĆ„rd, Blomkvist, & Orth-GomĆ©r, 2003;Houkes et al, 2011). Another strength of this study is that comparability is ensured because the instrument used in this study is one that is commonly used by researchers in occupational health in different contexts (Backteman-Erlanson et al, 2013;Lindeberg et al, 2010;Staland-Nyman, Alexanderson, & Hensing, 2008).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…20 For that reason, burnout has been a major topic of health services research in efforts to better understand its causes and solutions. [21][22][23][24][25] The most common measure of burnout is the Maslach Burnout Inventory (MBI), a well-validated, 26 widely-used self-survey measure. 27,28 The MBI comprises three scales: 1) emotional exhaustion (nine items), a state of chronic emotional and physical depletion; 2) depersonalization (five items), a sense of disconnection from coworkers and clients; and 3) diminished personal accomplishment (eight items), a negative sense of self-value and ability.…”
Section: Introductionmentioning
confidence: 99%